Total-factor Energy Efficiency in EU: Do Environmental Impacts Matter? - VlahiniÄ‡ Lenz, Nela; Å egota, Alemka; Maradin, Dario (International Journal of Energy Economics and Policy, 2018)
The concept of total-factor energy efficiency (TFEE) measures energy efficiency in a more superior and complex way within the total-factor framework, but takes only GDP as the only output. A new approach that includes desirable (GDP) and undesirable outputs (GHG emissions) has been developed recently and is applied in our research. The aim of our paper is to assess economy-wide energy efficiency in EU countries in a total-factor framework and compare these results with the environmental total-factor energy efficiency (ETFEE) that takes into account undesirable outputs like CO2 and SOx emissions. Our analysis is based on 2008-2014 panel data for 28 EU countries. The efficiency frontier is constructed by using DEA and modified SBM model based on data on three production factors (labor, capital and energy),GDPas desirable output and CO2 and SOx emissions as undesirable outputs. Our research results show that energy efficiency that does not incorporate environmental pollution is overestimated in 20 out of 28 EU countries. When analyzing environmental TFEE during time, results show that in 2014 there are more countries that have reached efficient frontier than in 2008, which could imply that EU countries pay a lot of attention to reduction of GHG emissions and sustainable development. Keywords: Total-factor energy efficiency, EU countries, DEA, undesirable outputs, environmental pollution JEL Classifications: Q43; Q56; C32; C61